ANALYSIS OF SCHOOL ERRORS OF CLASS VIII SMPN 19 PALU IN RESOLVING THE STORY OF PYTHAGORAS THEOREM BASED ON NEWMAN THEORY - Mirawati, Ni Kadek; Anggraini, Anggraini; Murdiana, I Nyoman; Sugita, Gandung (Prima: Jurnal Pendidikan Matematika, 2024)
This study aims to describe the types of errors made by students in solving Pythagorean theorem story problems based on Newman's theory. This type of research uses descriptive research with a qualitative approach. Data collection was done by tests and interviews. The type of data in this study is qualitative data, namely a description of the types of student errors in solving Pythagorean theorem story problems based on Newman's theory. The subjects of this research were students of class VIIIA SMP Negeri 19 Palu totaling 3 students. The results of this study indicate that students' errors in solving Pythagorean theorem problems in class VIIIA are 1) Comprehension Errors, namely students are unable to understand what is known and what is asked and students do not know what is known and what is asked according to the problem request 2) Transformation Errors, namely students do not write down the formula used, and students are unable to determine the correct formula in solving the problem. 3) Process Skill Errors, namely students do not write down the formula used, and students are unable to determine the correct formula in solving the problem. 3) process skill errors, namely students are unable to perform the procedures or steps used correctly, and students have not been able to perform the correct calculation process. 4) answer writing errors, namely students are unable to write the final answer from solving the problem, students are unable to write and explain the final answer in accordance with the intended conclusion of the problem